Agenda Setting Dynamics of Customary Tourism Village as an Effort to Preserve Tengger Culture in Ngadas Village - Ramadhani, Indira; Kusmana, Mochamad Attur Mehta; Aulia, Putri; Mustofa, Mustabsyirotul Ummah (Candidate: Jurnal Sains Politik, 2024)
NgadasÂ Village, a rural village located at the foot of MountÂ Bromo, East Java, Indonesia, has great potential in tourism and agriculture. This village is in the spotlight because of the diversity of cultures and traditions of theÂ TenggerÂ Tribe who have lived and maintained their customs which are derived from their ancestors. However, to gain official recognition as a customary village,Â NgadasVillage faces complex complexities and challenges that affect its approval process. This study aims to comprehensively understand the dynamics of the process of ratifyingÂ NgadasÂ Village as a tourism and customary village, with a focus on agenda setting and the obstacles encountered in the systemic agenda and institutional agenda. The research method used is a phenomenological qualitative approach, involving informants who have a deep understanding of the events and circumstances involved. The results of the study show that the local community and traditional leaders ofÂ NgadasÂ Village have played an active role in pushing for approval as a tourism and customary village. They realize the importance of cultural preservation and the need to uphold their traditional customs, which are gradually eroded by time.